Features of the vital capacity of the lungs in athletes engaged in underwater apnea - Tolstopyatov I.A.; Redi E.V.; Lisovik A.N. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assess the vital capacity of the lungs of athletes involved in underwater apnea among women and men of the highest sports skill. Methods and structure of the study. Submarine athletes aged from 22 to 28 years (30 women and 30 men) took part in the experiment. All athletes were conditionally divided into three groups of 20 people (10 women and 10 men): group A – athletes specializing in underwater apnea, group B – athletes specializing in stayer distances, group C – athletes specializing in sprint distances. Each athlete studied has specialized in this discipline of underwater sports for at least five years, is a member of the national team of the Krasnoyarsk Territory and has a sports title of at least candidate master of sports. Results and conclusions. The conducted research allows us to summarize that women and men involved in underwater sports and performing in the apnea discipline have high VC rates. Intense training regimes of highly qualified athletes in cyclic sports place increased demands on the external respiration apparatus, and scuba diving is precisely the sport where the cardiorespiratory system plays a significant role.